Antioxidant, Transcriptome and the Metabolome Response to Dietary Astaxanthin in Exopalaemon carinicauda - Li, Wenyang; Wang, Jiajia; Li, Jitao; Liu, Ping; Li, Jian; Zhao, Fazhen (Frontiers in Physiology, 2022)
Astaxanthin (Axn), a feed additive, is becoming increasingly important for modulating the metabolism, growth, development, and reproduction of aquatic organisms in aquaculture. In this study, the antioxidant, transcriptomic, and metabolomic analyses of the response of Exopalaemon carinicauda (E. carinicauda) after Axn feeding were investigated. Axn could reduce the content of malondialdehyde and increase the level of various antioxidant enzymes, which also proved that axn can improve the antioxidant capacity Transcriptomic analysis suggested that synthesis and secretion of immune proteins, cytoskeleton structure, and apoptosis signaling were altered after Axn feeding. The metabolic response to axn mainly includes the up regulation of different amino acids and the change of unsaturated fatty acids. Combined transcriptomic and metabolomic data indicated that amino acid metabolic pathways were upregulated in the muscles after Axn feeding. For good measure, energy metabolism pathways were upregulated in the muscles to increase ATP and unsaturated fatty acid production. This study provides key information to increase our understanding of the effects of Axn in shrimp.